2019
DOI: 10.3324/haematol.2018.205567
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen class II expression is a good prognostic factor in adult T-cell leukemia/lymphoma

Abstract: Attenuated human leukocyte antigen (HLA) class I expression is implicated as a major immune escape mechanism in several types of tumor. We previously reported that HLA class I/β2 microglobulin and programmed death ligand-1 expression are prognostic factors in adult T-cell leukemia/lymphoma. A recent report suggested that HLA class II expression is also an important prognostic factor for the clinical outcome of programmed death-1 blockade therapy in recurrent/refractory Hodgkin lymphoma. This prompted us to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…Several studies, including ours, have identified that the expression of several proteins and genomic alterations is related to the prognosis of ATLL. 15,16,19,20 Additionally, ATLL prognosis is improved by an anti-CCR4 antibody and stem cell transplantation. [34][35][36][37] Notably, none of the patients were treated with anti-CCR4 antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, including ours, have identified that the expression of several proteins and genomic alterations is related to the prognosis of ATLL. 15,16,19,20 Additionally, ATLL prognosis is improved by an anti-CCR4 antibody and stem cell transplantation. [34][35][36][37] Notably, none of the patients were treated with anti-CCR4 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells detected morphological features, including cell size, nuclear atypia such as distinct chromatin, prominent nucleoli, irregular shaped nuclear contours, and so on, as reported in previous studies. 15,19 Vessels and fibroblasts are negative for TACC3, so staining works properly as they are negative controls.…”
Section: Definition Of Immunohistochemical Tacc3 Score and Cutoff Vmentioning
confidence: 99%
“…1 All cases were included in our previous study. [25][26][27] The study was approved by the Research Ethics F I G U R E 1 Representative histological (H&E) and immunohistochemical staining of CD47 in ATLL (original magnification, ×400) F I G U R E 2 Histograms for immunohistochemistry, with distribution of the rate of CD47-positive tumor cells. The cut-off points are shown as the median Committee of Kurume University and was conducted in accordance with the Declaration of Helsinki.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described. 11,12 Antibodies are listed in Table S1.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%